Comparison and Phylogenetic Analysis of Mitochondrial Genomes of Talpidae Animals - Di Xu; Mengyao Sun; Zenghao Gao; Yiping Zhou; Qingqian Wang; Lei Chen (Animals, 2023)
Talpidae is a model group for evolutionary studies due to their highly specialized morphologies and diverse lifestyles. Mitochondrial genomes are molecular markers commonly used in species evolution and phylogenetic studies. In this study, the complete mitochondrial genome sequence of Scaptochirus moschatus was obtained by Illumina NovaSeq sequencing. The complete mitochondrial genomes of 14 Talpidae species (including Scaptochirus moschatus obtained in the present study) and the cytochrome b (Cyt b) gene sequences of 48 Talpidae species were downloaded from the NCBI database for comparison and phylogenetic studies to analyze the phylogenetic relationships and to find the possible reasons of the niche differentiation and ecotype specialization of Talpidae animals. The results showed that the mitochondrial genome sequences of 14 species belonging to the family Talpidae were 16,528 to 16,962 bp, all containing 13 protein-coding genes, 22 tRNA, two rRNA, and a non-coding region (control region). The difference in the number of repetitive repeats in the control region is responsible for the difference in the length of Talpidae mitochondrial genome sequences. Combining the divergence time of Talpidae animals with the geological history, it is found that the niche differentiation and ecotype divergence of Talpidae is closely related to historically global climate changes. Semi-aquatic groups diverged in the early Oligocene (about 31.22 MYA), probably in response to the global climate transition from warm to cool. During the early Miocene (about 19.54 MYA), some species of Talpidae moved to underground habitats and formed fossorial groups that were adept at digging due to the effects of the glaciation. In the middle Miocene (about 16.23 MYA), some Talpidae animals returned to the ground and formed semi-fossorial shrew moles as global climate warming again.